Strengthening The Students' Value of Diversity in Learning in Global Era - Hasan, Karnadi (International Journal of Active Learning, 2017)
Religious education as the basis of formation of students is basically a form of internalization of the value of faith and devotion (Imtaq) through the vehicle of school education. The importance of the Imtaq coaching, because religious education paying attention to all aspects of student potential (Supriyadi, 2004: 123), which includes manners (inner strength, character), mind (intellect), and body (Dewantara, 1977); Cognitive, affective, and psychomor (Blomm et al., 1981); Thinking, acting, and feeling (Gable, 1986); Smart and good (Lickona, 1992); Intelligence quotiont, emotional quotion, and spiritual quotiont (Agustian, 2001), to be a faithful and devout human being to God Almighty, to be noble, healthy, knowledgeable, capable, creative, independent and to be a democratic and responsible citizen (UUSPN Number 20 Year 2003, Article 3). The implementation of religious education in schools as an effort to develop the values and attitudes of religious students, will be effective when using an integrative approach. Such approaches include: (1) creation of a school culture which is conducive to the growth of Imtaq, (2) Imtaq material integration into other non-religious education subjects, (3) extracurricular activities that contain Imtaq, and (4) Cultivate school cooperation with parents and community in the guidance of Imtaq students. Strengthening students' religious values in schools can occur from: (1) creation of school culture, which includes school discipline, learning facilities, and teacher competence; (2) learning process of religious education; (3) learning result competence; And (4) the religiosity of students in the community related to belief, religious practices, and religious behavior (the consequences). This article is the main idea of strengthening the values of religious students as an effort to establish noble character and enrichment of information for observers of religious education in schools.